Salinity–temperature interaction drives metabolic and energetic changes in an Arctic crustacean - Bourdin, Pauline; Mottola, Giovanna; von Weissenberg, Ella; Daase, Malin; Engström-Öst, Jonna; Anttila, Katja (Ecological Society of America, 2026)
The Arctic is shifting towards a prevalence of warm and more saline Atlantic-like waters. These changes in the marine environment pose significant challenges for the ecophysiology of marine invertebrates. Here, we measured the metabolic enzyme activity of citrate synthase and lactate dehydrogenase, as well as the energy content and level of oxidative damage in 71 individuals (~10–14 individuals/station) of Thysanoessa inermis collected in six fjords in Svalbard that were characterized by different levels of influence of Atlantic water and, thus, temperature and salinity variability in the water column. T. inermis inhabiting fjords with strong influence of Atlantic water masses had lower lipid and protein content, and higher anaerobic metabolism compared to those from more Arctic fjord types, with Isfjorden driving mostly such difference. Moreover, T. inermis collected in fjords with high variability in both temperature and salinity had lower lipid content than that in stations with more stable temperature and salinity. Our results suggest that T. inermis in fjords influenced by Atlantic waters is possibly under stress leading to increased metabolism, consequently enhancing energy consumption. If the energy consumption is not compensated for, by an uptake, it could result in a decrease in the total biomass of T. inermis with possible consequences for the entire Arctic food web.